Onshore tin mining waste treatment - Teerapon Soponkanaporn; Samorn Muttamara; Chongrak Polprasert; Lohani, Bindu N.; The Australian Government (Bangkok : Asian Institute of Technology, 1979)
The wastewater from tin mine is rich in inorganic suspended solids. The flow rate was nearly constant at 285 m3/h and the suspended solids concentration varied from 3 to 26 g/t. Since the wastewater does not meet either the mineral acts or the existing effluent standards, particularly in term of suspended solids, this treatment studies was conducted. The treatment process consisted of primary sedimentation, coagulation and secondary sedimentation. The suspended solids removal efficiency in primary sedimentation was found to be 98% at detention time of 1.5-2.5 hand an overflow rate of 0.009-0.014 m3/min-m2 {u2022} Chemical treatment of the effluent from primary sedimentation with alum was found to be most economic at a dosage of 6 mg/t. The secondary sedimentation with a detention time of 2.0-3.0 h and overflow rate of 0.007-0.011 m3/min-m2 could give superannuant suspended solids of 30 mg/t. Sludge from the secondary sedimentation (3.5%) can be disposed off into the abandoned deep mine according to the minerals act. The continuous treatment study with a lab-scale unit has confirmed the effectiveness of" the alum dose. In the second part of the research study conducted on the short terms effect of suspended solids, no mortality of coral Poritidal Goniopora· was observed ever up to a concentration of 500 mg/t for 96 hours. However they show a sign of stress at suspended solids concentration of more than 30 mg/t by secreting mucus to cover their polyps. The amount of stress varied directly with the concentration of suspended solids.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1979
Keywords: Factory and trade waste